2019
DOI: 10.1002/acm2.12551
|View full text |Cite
|
Sign up to set email alerts
|

Geometric and dosimetric impact of anatomical changes for MR‐only radiation therapy for the prostate

Abstract: Purpose With the move towards magnetic resonance imaging (MRI) as a primary treatment planning modality option for men with prostate cancer, it becomes critical to quantify the potential uncertainties introduced for MR‐only planning. This work characterized geometric and dosimetric intra‐fractional changes between the prostate, seminal vesicles (SVs), and organs at risk (OARs) in response to bladder filling conditions. Materials and methods T2‐weighted and mDixon sequences (3–4 time points/subject, at 1, 1.5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…Nejad-Davarani et al [19] studied the dosimetric effect of anatomical changes in prostate cancer patients for an MRI-only workflow. MR images of volunteers with both full and empty bladder were acquired, with 45 min apart.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nejad-Davarani et al [19] studied the dosimetric effect of anatomical changes in prostate cancer patients for an MRI-only workflow. MR images of volunteers with both full and empty bladder were acquired, with 45 min apart.…”
Section: Discussionmentioning
confidence: 99%
“…Intrafractional prostate motion is a well-known phenomenon [12][13][14][15][16][17][18][19] and can have dosimetric impact. Nejad-Davarani et al [19] found a 20.2% decrease in the dose to 95% of the volume (D 95% ) in the PTV due to prostate displacement occurring during approximately 45 minutes (min). There are various reasons for prostate displacements, such as bladder filling, rectum activity and patient motion due to muscle tension or leg motion [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both are shown in Figure 2. First, spatial 2D/3D views (Figure (a)) allow the experts to see how the dose affects the tumor and its surrounding organs for a given point in the treatment period [19]. This approach does not support an easy exploration of multiple patients or multiple fractions at the same time-an important aspect for judging the robustness of treatment strategies.…”
Section: Current Workflowmentioning
confidence: 99%
“…Instead, if a specific group 17is selected, it is brought forward with a F+C strategy in the 2DFigure 7 (c)) and the 3D views. On demand, the 3D view can19 show the explicit encoding of the surface variations(Figure 7…”
mentioning
confidence: 99%